Claims and frames: newspaper coverage of the human papillomavirus vaccine - Shenk, Caitlin, author; Trumbo, Craig, advisor; Broadfoot, Kirsten J., committee member; O'Keefe, Garrett J., committee member (Colorado State University. Libraries, 2010)
Human papillomavirus, or HPV, a common sexually transmitted infection, has been identified as a primary cause of cervical cancer. With the availability of HPV vaccines, accurate and understandable information about HPV and HPV vaccines will be essential to manage personal and public responses to HPV and vaccine risks. The media play a key role in providing the public with that information. This content analysis quantitatively explored media treatment of risk associated HPV and the HPV vaccine through the theoretical lenses of framing and claims-making. A coding schema was developed to identify and quantify recurring information, frames, and claims-makers in coverage. Overall, coverage addressed a breadth of background and risk information about HPV and the HPV vaccine, but lacked a depth of discussion that would better inform readers. Dominant frames emphasized moral judgments, positive benefits, preventative behaviors, episodic contexts, institutional responsibility, and ethical values. Claims-makers more commonly made claims about the HPV vaccine over HPV, and the types of claims-makers included for each were relatively consistent. Although the media are not explicitly tasked with educating people on all the facts and perspectives about HPV and HPV vaccination, it is important to recognize their influence on the health and risk information people receive. Media coverage of HPV and the HPV vaccine could better inform the public by including more detailed background and risk information and by emphasizing a broader range of frames and claims-makers to provide readers with a more comprehensive understanding of the scope and implications of these issues.
Department Head: Greg Luft.